Molecular Characterization of Prothionamide-Resistant Mycobacterium tuberculosis Isolates in Southern China - Tan, Yaoju; Su, Biyi; Zheng, Huiwen; Song, Yuanyuan; Wang, Yufeng; Pang, Yu (Frontiers in Microbiology, 2017)
Prothionamide (PTH) has been widely used in the treatment of tuberculosis (TB), especially multidrug resistant tuberculosis (MDR-TB), while data regarding prevalence of resistance-causing mutation is limited. In this study, we aimed to investigate the molecular characteristics of PTH-resistant MTB isolates, and also analysed the risk factors for PTH resistance among Mycobacterium tuberculosis (MTB) isolates in southern China. A total of 282 MTB isolates were enrolled in from Guangzhou Chest Hospital. Among these isolates, 46 (16.3%) were resistant to PTH. Statistical analysis revealed that PTH resistance was more likely to be associated with resistance to levofloxacin (LFX) (OR: 2.18, 95% CI: 1.02-4.63; P=0.04). Of the 46 PTH-resistant MTB isolates, 37 (80.4%) isolates harbored 19 different mutation types, including 10 (21.7%) isolates with double nucleotide substitutions and 27 (58.7%) with single nucleotide substitution. The mutations in ethA (50.0%, 19/38) were most frequently observed among PTH-resistant isolates, followed by 16 (42.1%) in the promoter of inhA and 6 (15.8%) in inhA. In addition, no significant difference was found in the distribution of isolates with different mutation types between Beijing and non-Beijing genotypes (P>0.05). In conclusion, our data demonstrate that high diversity of genetic mutations conferring PTH resistance is identified among MTB isolates from southern China. Mutations in inhA, ethA, mshA, and ndh genes confer increased resistance of MTB to PTH. Ancient Beijing genotype strains have higher proportion of drug resistance compared with modern Beijing strains. In addition, PTH resistance is more likely to be observed in the LFX-resistant MTB isolates.